Effect of Biological and Chemical Ripening Agents on the Nutritional and Metal Composition of Banana (Musa spp) - C M Sogo-Temi; O A Idowu; E Idowu (Journal of Applied Sciences and Environmental Management, 2014)
The use of potentially toxic ripening agents is common in developing countries. Four ripening agents namely calcium carbide, potash, African mango and jathropha curcas leaf were used and compared with a control with no ripening agent. Result showed that RB1 and RB2 were the first to ripen at 3days with RB5 at 6th day. Protein content reduced in the ripened samples in the order of 4.12>3.68>3.04>2.52>1.99>1.77%. Protein value was lowest when calcium carbide was used. Fat ash and fiber contents range between 0.28-1.72, 0.75-2.75and 0.50-1.75% respectively. The moisture content increased from 65.50 to 74.0%, while carbohydrate content range is 17.49-29.29%. Pb, Cu, Zn and Mn values of 0.22, 0.87, 1.96 and 0.67ppm was highest in calcium carbide ripened banana and lowest in the control 0.09, 0.26, 0.37 and 0.19 ppm.